Glycosaminoglycans in the urinary bladder mucosa, tumor tissue and mucosal tissue around tumor - Bojanić Nebojša; Nale Đorđe; Mićić Sava; Lalić Nataša; Vuksanović Aleksandar; Tulić Cane (Vojnosanitetski Pregled)
Introduction/Aim. Glycosaminoglycans (GAG) are one of the main constituents of the connective tissue and cellular membrane. Their presence has been evidenced in mucosa and muscular tissue of the urinary bladder of both healthy individuals and those affected by carcinoma. This suggest their potential role in the onset of bladder carcinoma and follow-up of those patients. The aim of the study was to determine GAG levels in tumor tissue and the surrounding bladder mucosa in patients with bladder tumor, as well as in the bladder mucosa in patients with bladder carcinoma, and to compare the results according to the grade and stage of tumor and relapse. Methods. Tissue samples were taken in 61 patients (48 males and 13 females), mean age 61.5 years, range 40-92 years, obtained by transurethral resection (TUR) of bladder tumor, and 8 healthy persons. Determination of a total GAG content in the tissue samples was done by the Whiteman's method and then compared regarding the tumor grade and stage. Results. Tumor grade and stage directly correlated with the levels of GAG. The GAG levels were significantly higher in tumor samples as compared to healthy mucosa. Conclusion. Higher GAG levels were recorded in all the patients with bladder tumors comparing to smples obtained from healthy individuals. GAG levels do not predict tumor relapse.